APPLICATION OF AUTOMATIC ARC INJECTION MOLDING TECHNOLOGY IN PIPE PRODUCTION AND REPAIR - Tadjikuziev Rakhmatjan Makhamadovich (European Science Publishing, 2024)
The essence of this article is the construction structures in the production enterprises of all industrial sectors in our country, the constructions for the delivery of oil and oil products to the places, the drinking water and water-waste complexes in the territories of the Republic, the above-ground and underground main pipelines, the equipment brought from foreign companies and used. Problems arise in the production, repair and maintenance of all kinds of pipes, tubes and pipes in parts and mechanisms. This article explains how important such a problem is in the machine-building industry and how the technology of automatic flux-cored arc welding is carried out.
Keywords: Fluxes, slag, arc welding, non-ferrous metal, powders, sheet plates, chemical alkalis, spray mechanism, pipe, non-metallic materials, pipes, electrode, metal layer, alloys.